Relationship of Knowledge and Attitude to Pulmonary TB Prevention Behavior in Home Contact in The Working Area of Puskesmas Batuputih in 2020 - EL GARRY RADJAH; Pius Weraman; Honey Ivone Ndoen (Journal of Health and Behavioral Science, 2021)
Tuberculosis is an infectious disease caused by mycobacterium tuberculosis. The disease is transmitted by air (airbone disease). Tuberculosis cases in Batuputih Health Center in the last 4 years have experienced a significant increase in cases. In 2017 there were 4 cases of tuberculosis and in 2020 there were 32 cases of tuberculosis. This study aims to analyze the relationship of knowledge and attitudes to tuberculosis prevention behavior in house contact at Batuputih Health Center. This research is an analytical survey research with cross-sectional method. samples in this study numbered 60 people. The data was analyzed using chi square test with a meanness level of α=0.05. The results showed that 81.9% of family members who were home with sufferers had positive preventive behavior. This study shows that there is a knowledge relationship to tuberculosis prevention behavior (p=0.001) and attitude towards tuberculosis prevention behavior (p=0.002).